Signe et signification à l’aune de la dichotomie syntaxe / sémantique - Manuel Gustavo Isaac (Corela)
This paper analyses three different theories of meaning based on a binary model of the sign. The ones of Frege, Husserl and Saussure. The two first ones belong to a same paradigm. They develop two opposite conceptions of meaning – extensional Frege’s case, intensionnal in Husserl’s one – which contributes to set up, with opposite perspectives, the dualisation of syntax and semantics. Consequently, their paradigm is then opposed to the structural semiology of Saussure in which the interaction between syntax and semantics is internalised at the level of the system that the signs integrate. The purpose of this paper is therefore to explicit a possible reason for the divergence of two major conceptions of meaning that have organised the development of concurrent trends all along the linguistics of the 20th century, a formal one and a structural one.